MENAPAKI DISTINGSI GENEOLOGIS PEMIKIRAN PENDIDIKAN - Zainal Abidin (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Muhammadiyah and Nahdlatul Ulama it’s due of moslem organization in Indonesia since the colonial period until present day, both of them are the biggest Islamic Organization, and works in the dakwah and Islamic Education in Indonesia modern era. For many times ago Muhammadiyah and Nahdlatul Ulama have some different in religion orientation and practice in a branch doctrines of whole Islamic tradition. The fonders of Muhammadiyah is KH. Ahmad Dahlan, in Yogyakarta 1912. Muhammadiyah is represent as modern moslem, because it’s the Islamic organization with members and built in by moslem scholars, and they have spirit to purificated of Islamic doctrines from al-Qur’an and al-Hadits, so that Muhammadiyah called also as modern Islamic organization. But Nahdlatul Ulama (NU) it’s the traditional Islamic Organization because NU built in the traditional ulama of Islam in Indonesia, and the founder of this organization is KH. Hasyim Asy’ari in Surabaya 1926. In generally , Ulama in NU, They are alumni of Islamic traditional institution its called Pesantren. As a organization NU have characteristic as Islamic traditional organization, because NU playing very important in the protect of tradition of ulama madzhab in Islam like Syafi’i, Maliki, Hambali, and Hanafi, and NU is very famous organization as Ahlusunnah wal Jama’ah (Aswaja), and for established the doctrine of Aswaja, NU have some Islamic institution like pesantren to give some Islamic knowledge for santri (student) who learned in those institution of Islamic education.